2008
DOI: 10.1002/clen.200700171
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Ciprofloxacin in Brazilian Hospital Effluent and Preliminary Risk Assessment: A Case Study

Abstract: This study was carried out to evaluate the occurrence of the fluoroquinolone antimicrobial agent ciprofloxacin (CIP) in the effluent of the Hospital of the Federal University of Santa Maria (HUSM). Measured environmental concentrations (MECs) of CIP in the hospital wastewater, both before (P1) and after (P2) cesspit/filter system treatment (CFTS), were determined by means of solid phase extraction and reversed-phase liquid chromatography with fluorescence detection (LC-FLD) and reversed-phase liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
1
47
0
3
Order By: Relevance
“…The antibiotic groups that have been analyzed up to now include a number of different important classes of antibiotics. They include primarily macrolides, aminoglycosides, tetracyclines, sulfonamides, sulfanilamides, and quinolones to name just a few [14,[23][24][25][26][27][28][29]. Erythromycin-H 2 O up to 287 [34,35] up to 49 [36] up to 6000 up to 1700 [8] up to 190 [33] up to 15.9 [37] up to 220 [38] up to 400 [30] Clarithromycin up to 328 up to 65 [34,35] up to 240 up to 260 [8] up to 37 [33] up to 20.3 [37] up to 20.3 [39] up to 38 [30] Roxithromycin up to 68 [30] up to 72 [34,35] up to 26 [36] References up to 1000 up to 560 [8] up to 14 [33] up to 180 [38] up to 350 [31] Chinolones Fluorchinolone up to 100 up to 5 [32] Fluorchinolone up to 106 up to 19 [34,35] Ciprofloxacin 9 [33] up to 30 [38] up to 26.2 [37] up to 1300 [31] up to 26 [39] Norfloxacin up to 120 [38] Ofloxacin up to 82 [30] 20 [33] Sulfonamides Sulfamethoxazole up to 370 [...…”
Section: Occurrencementioning
confidence: 99%
“…The antibiotic groups that have been analyzed up to now include a number of different important classes of antibiotics. They include primarily macrolides, aminoglycosides, tetracyclines, sulfonamides, sulfanilamides, and quinolones to name just a few [14,[23][24][25][26][27][28][29]. Erythromycin-H 2 O up to 287 [34,35] up to 49 [36] up to 6000 up to 1700 [8] up to 190 [33] up to 15.9 [37] up to 220 [38] up to 400 [30] Clarithromycin up to 328 up to 65 [34,35] up to 240 up to 260 [8] up to 37 [33] up to 20.3 [37] up to 20.3 [39] up to 38 [30] Roxithromycin up to 68 [30] up to 72 [34,35] up to 26 [36] References up to 1000 up to 560 [8] up to 14 [33] up to 180 [38] up to 350 [31] Chinolones Fluorchinolone up to 100 up to 5 [32] Fluorchinolone up to 106 up to 19 [34,35] Ciprofloxacin 9 [33] up to 30 [38] up to 26.2 [37] up to 1300 [31] up to 26 [39] Norfloxacin up to 120 [38] Ofloxacin up to 82 [30] 20 [33] Sulfonamides Sulfamethoxazole up to 370 [...…”
Section: Occurrencementioning
confidence: 99%
“…It was reported that over thirty-five main rivers surrounding the Bohai Sea were severely polluted (Jun, 2007;Mao et al, 2009) and transported 36% of wastewaters and 47% of the solid pollutants to the Bohai Sea (Wang and Wang, 2007). Increasing use of antibiotics in aquaculture is another important source for the marine environment (Jia et al, 2011;Kümmerer, 2009;Martins et al, 2008;Minh et al, 2009;Wille et al, 2010;Xu et al, 2007;Zou et al, 2011). The Bohai Sea is the only continental sea in China and has a low exchange rate of seawater, resulting in the long-term residence of pollutants in the sea .…”
mentioning
confidence: 99%
“…In raw sewages and the secondary effluents from sewage treatment plants, 10 quinolones antibiotics were found and the concentrations ranged from 0.1 to 2.6 lg/L and 0.05 to 1.0 lg/L, respectively (Tong et al, 2011;Jia et al, 2012). It is worth noting that ciprofloxacin have also been detected in untreated hospital sewages at a level of 101 lg/L (Lindberg et al, 2004;Martins et al, 2008).…”
Section: Introductionmentioning
confidence: 93%